[Translated article] Frontal Examination of the Distal Nail Unit - L. Navarro Campoamor (Elsevier, 2024)
Clinical findings in many nail disorders are not usually pathognomonic. An accurate diagnosis therefore relies on inspection of the nail unit from different angles. We review clinical features of different nail disorders that can be observed during frontal examination of the distal edge of the nail plate and the hyponychium and correlate these with features observed when the nail is viewed from above. Frontal examination of the distal nail unit can help establish a clinical diagnosis in routine practice. Resumen: Los signos clínicos que acompañan a muchas alteraciones ungueales habitualmente no son patognomónicos de ninguna enfermedad concreta. Por tanto, la exploración del aparato ungueal desde diferentes ángulos de visión es fundamental para realizar un diagnóstico acertado. En el presente artículo se revisan los signos clínicos que pueden obtenerse mediante la exploración frontal del borde distal de la lámina ungueal y el hiponiquio, y se correlacionan con los signos de la exploración aérea. Dicho abordaje permite facilitar el diagnóstico clínico de la enfermedad ungueal en la práctica diaria.